2019
DOI: 10.1186/s13059-019-1652-0
|View full text |Cite|
|
Sign up to set email alerts
|

Epigenetic signatures associated with imprinted paternally expressed genes in the Arabidopsis endosperm

Abstract: Background Imprinted genes are epigenetically modified during gametogenesis and maintain the established epigenetic signatures after fertilization, causing parental-specific gene expression. Results In this study, we show that imprinted paternally expressed genes (PEGs) in the Arabidopsis endosperm are marked by an epigenetic signature of Polycomb Repressive Complex2 (PRC2)-mediated H3K27me3 together with heterochromatic H3K9me2 and CHG methyl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 46 publications
3
51
0
Order By: Relevance
“…Our data obtained in this ( Figure 2 (Figure 2c), genes with H3K27me3/H3K9me2 but unmethylated CHG on REF6-binding sites were not significantly biased (Figure 8a, gray boxes). This data suggests that triple repressive marks are associated with paternally-biased gene expression in germinating endosperm, similar as in the developing endosperm (Moreno-Romero et al, 2019;Moreno-Romero et al, 2016). In contrast, genes with single H3K27me3 and unmethylated REF6-binding sites were significantly maternally biased (Figure 8b, upper orange boxes), supporting the idea that genes with single H3K27me3 are reactivated during germination.…”
Section: Parentally-biased Expression During Germination Is Regulatedsupporting
confidence: 63%
See 1 more Smart Citation
“…Our data obtained in this ( Figure 2 (Figure 2c), genes with H3K27me3/H3K9me2 but unmethylated CHG on REF6-binding sites were not significantly biased (Figure 8a, gray boxes). This data suggests that triple repressive marks are associated with paternally-biased gene expression in germinating endosperm, similar as in the developing endosperm (Moreno-Romero et al, 2019;Moreno-Romero et al, 2016). In contrast, genes with single H3K27me3 and unmethylated REF6-binding sites were significantly maternally biased (Figure 8b, upper orange boxes), supporting the idea that genes with single H3K27me3 are reactivated during germination.…”
Section: Parentally-biased Expression During Germination Is Regulatedsupporting
confidence: 63%
“…Genomic imprinting leading to maternally-biased expression is predominantly connected to DNA demethylation of maternal alleles mediated by the DNA glycosylase DEMETER (Gehring et al, 2009;Hsieh et al, 2011;Park et al, 2016). In contrast, paternally-biased expression is predominantly connected to the presence of H3K27me3, H3K9me2, and CHGm on maternal alleles (Klosinska et al, 2016;Moreno-Romero et al, 2019;Moreno-Romero et al, 2016;Moreno-Romero et al, 2017). The FIS-PRC2 establishes H3K27me3 in the central cell, which is maintained on the maternal alleles after fertilization.…”
Section: Introductionmentioning
confidence: 99%
“…P-values were determined using two-tailed Mann-Whitney tests. ( b ) Fraction of Cluster 1 and Cluster 2 binding sites that target PEGs (Figure 4—source data 1) and putative PEGs (Moreno-Romero et al, 2019). ( a, b ) H3K27me3 clusters are those defined in Figure 4b.…”
Section: Resultsmentioning
confidence: 99%
“…To determine parental gene expression ratios in 2x and 3x seeds, we used previously generated endosperm gene expression data (Martinez et al, 2018). In this dataset, L er plants were used as maternal plants pollinated with wt Col or osd1 Col plants, allowing determination of the parental origin of sequenced reads following the method described before (Moreno-Romero et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Following publication of the original article [1], the authors reported that Additional file 4, “Table S5. Parent-of-origin RNAseq dataset of 4 DAP INTACT-purified endosperm of Col × L er reciprocal crosses” had the following error: Column 6, labeled as “Reads_Mat_Ler”, should say “Reads_pat_Col”.Column 7, labeled as “Reads_pat_Ler”, should say “Reads_mat_Ler”.…”
mentioning
confidence: 99%